Estudo do potencial antitumoral de alguns complexos de Pt(II), Cu(II) e Ga(III) - Ivina Paula de Souza (2011)
This work reports on the antitumoral potential of ten metallic complexes, previously characterized, seven of them being of Pt(II), two of Cu(II) and one of Ga(III). Among the platinum(II) complexes, 1, 2, and 3 are complexes of cisplatin and aminoacids; 4 and 5 of cisplatin and purinic ligands; and 6 and 7 are Pt(II) complexes with two antibiotics used in thetreatment of tuberculosis, the pyrazinamide and the isoniazide, respectively. 8 and 9 are compounds of Cu(II) and 10, a Ga(III) complex. The goals of this work were: i) to study the effect of the complexes on the growth of tumor cells; ii) to study the uptake of the most activePt(II) complexes by tumor cells; iii) to study the interaction of the most active complexes with DNA; and iv) to study the interactions of the complexes able to bind DNA with a nucleotide model. The most important use of metallic complexes in medical practice is in the treatmentof cancer. DNA, due to its importance in the cellular cycle, is one of the main targets for antitumorals. Aiming to elucidate the mechanism of action of the most active compounds, a study of their interactions with DNA was undertaken by UV-Vis spectrophotometry, and witha nucleotide model, the guanosine 5'-monophosphate by mono-dimensional 1H, twodimensional 1H COSY and 31P NMR spectrometry. Besides the elucidation of the mechanismof action, another fundamental aspect is the study of cellular uptake of the compounds, since a sufficient amount of drug must accumulate inside cells and, more specifically, in the nucleus. The intracellular platinum concentration was assessed by flameless atomic absorptionspectrometry. For all compounds, the concentration required to inhibit 50 % of cell growth, the IC50, was determined in a chronic mielogenous leukemia cell line, the K562. Complexes 1, 2, and 5 did not show a significant cytotoxic activity whereas 3, 4, 6, and 7 have exhibited aconsiderable activity, with IC50 values of 2.93, 1.00, 6.34, and 24.4 ìmol L-1, respectively. In all cases, coordination to Pt(II) ions led to an increase in the activity, since the IC50 of all complexes was inferior to that of free ligands. A good correlation between cytotoxic action and intracellular platinum concentration was found, after incubating cells with equitoxicconcentrations of 3, 4, 6, and 7. The incubation with IC50 doses led to an intracellular platinum concentration of 2.18 x 10-16; 0.47 x 10-16; 2.65 x 10-16, and 23.18 x 10-16 mol cell-1, for 3, 4, 6, and 7, respectively. These results are important because they indicate that the observed cytotoxic effect is directly related to the presence of platinum. Compounds 4 and 6form a ternary complex with DNA, with the affinity constants of 1.45 x 105 and 5.92 x 103,8 respectively. Complex 4 was the most active and showed an affinity to DNA approximately 25 times higher than that of 6. The interactions between 3 or 6 and the guanosine 5'- monophosphate were studied by NMR. The results obtained indicate that complex 3 binds to N7 of the nitrogenated base. For complex 6, the formation of a quelate, in which platinum(II) coordinates to 5'-GMP via N7 and one of the oxygens of the a-phosphate group, was proposed. The obtained results suggest that the mechanism of the cytotoxic activity of the platinum(II) complexes studied may involve an interaction with DNA and that N7 of guaninecan be the site of this interaction. The Cu(II) complexes, 8 and 9, showed relatively high IC50 values and were discarded as potential antitumoral agents. Finally, the gallium(III) complex, or complex 10, was very active with the IC50 of 1.80 ìmol L-1. The formation of a ternary species between 10 and DNA, with the affinity constant of 5.67 x 104, was evidenced. Thecoordination of gallium to the nucleotide 5'-GMP was proposed to occur through an a-phosphate oxygen. Complex 10 can be considered a promising antitumoral agent.